Fluid-Structure Interaction Simulation of Excess Flow Valve Movement at Different Operating Pressures and Gas Flow Rates - G. Coşkun; H. Pehlivan (Journal of Applied Fluid Mechanics, 2021)
Excess Flow Valves (EFV) for gas-stop systems is generally used in natural gas pipelines to prevent possible damages or destruction due to gas leakage. It can be used in a wide operating range of pressure, but the shut-off flow rate could be in various values at different pressures since natural gas can easily be compressed and can reach higher density. In this study, shut-off and nominal gas flow which effect on a spring force attached to an EFV system simulation by using Fluid Solid Interaction (FSI) strategy was studied. Furthermore, User Define Function (UDF) adapted to simulation to obtain the time-dependent deformation of the spring. The simulations were repeated at five different operating pressures (1-5 bar) with changing flow rates to show if EFV can shut-off the system or not. Results were validated against experimental data of the EFV to show the consistency of the FSI strategy. Moreover, detailed behaviour information of the EFV obtained by means.